SOME CHARACTERIZATIONS OF SLIGHTLY Σα - COMPACT FUZZY SETS - Md. Abdul Mottalib Talukder; B. M. Khalid Hossain (Journal of Mechanics of Continua and Mathematical Sciences, 2025)
Within this paper, we create the ideas of slightly Σα -shelter, shortly sΣα - shelter, and slightly Σα - compact, shortly sΣα - compact fuzzy sets. In addition, we have established certain theorems concerning our vision in fuzzy topological spaces, fuzzy subspaces, fuzzy continuity mapping, fuzzy open mapping, fuzzy 2 T -spaces (Hausdorff spaces), and their different characterizations. Finally, we have discussed our vision about the “good extension” characteristics.